Semillas del Paleozoico Superior de Argentina: su utilización bioestratigráfica (Ameghiniana, 2014)
The biostratigraphic and lithostratigraphic distribution of Late Paleozoic seeds in Argentine is analyzed. Accordingly, taxa with biostratigraphic value me established for intra- and extra-basin correlations. Comparisons with other related seed taxa from Gondwana suggest that seeds can be only important as biostratigraphic markers in regional or basinal scales.